A critical reflection on the development of the Participatory Autism Research Collective (PARC). Issue 2 (1st April 2019) - Milton, Damian Elgin Maclean; Ridout, Susy; Kourti, Marianthi; Loomes, Gillian; Martin, Nicola
Abstract : Purpose: The Participatory Autism Research Collective (PARC) was initially set up with the purpose of bringing autistic people, including scholars and activists (but not exclusively), together with early career researchers and practitioners who work with autistic people, with the aim being to build a community where those who wished to see more significant involvement of autistic people in autism research could share knowledge and expertise. This paper aims to discuss this issue. Design/methodology/approach: This paper explores the development of the PARC network, reflecting upon its activities and ethos within current higher education practices and structures. Findings: In supporting autistic individuals in their attempts to establish themselves within academic systems that may not always be considerate or accommodating, the existence of PARC creates a structure with which autistic people can influence social change. PARC serves as a network of support, strengthening the presence of autistic scholars in academia. It also provides a structure through which autistic people are able to demonstrate helpful practices with which to engage more broadly. Originality/value: The PARC network is the first autistic-led venture of its kind in the UK to have a sustained impact. PARC is growing to become an important element in the field of autism studies both by supporting emerging autistic academics and by promoting ethical and participatory research methods and practices.